Do Tax Reforms Improve Revenue Mobilization? Evidence from Ghana Using ECM and ARIMA Forecasting - William Bekoe; John Kwaku Amoh; Kwadwo Opok; Joseph Danquah Ansong (Lembaga Penelitian dan Ilmu Pengetahuan JEPIP, 2025)
This study evaluates the effectiveness of tax reforms on revenue mobilization in Ghana over the period 2000 to 2024. Using annual revenue data from the Ghana Revenue Authority (GRA), the analysis integrates multiple econometric approaches, including structural break identification, unit root diagnostics, an error correction model (ECM), and ARIMA forecasting. The findings reveal significant structural breaks in 2004, 2011, and 2016, which correspond to major reform episodes and external commodity shocks, indicating that policy changes have had measurable impacts on revenue performance. Stationarity tests confirmed that revenue is integrated of order one, justifying the use of the ECM to capture both short-run dynamics and long-run equilibrium relationships. The ECM results highlight a significant and negative error correction term of approximately 0.857, suggesting that roughly 86% of deviations from the long-run path are corrected within one year, thereby demonstrating the resilience of Ghana's fiscal adjustment mechanism. Forecast results project sustained revenue growth, with collections expected to exceed GH₵194 billion by 2025, assuming no major disruptions. Collectively, these results provide robust evidence that tax reforms have enhanced Ghana's revenue mobilization capacity, though the system remains sensitive to external shocks, particularly commodity price fluctuations and currency depreciation. The study underscores the importance of sustaining reforms and deepening revenue digitalization to ensure long-term fiscal stability.